Top-Down Disconnectivity in Schizophrenia During P300 Tasks - Li, Fali; Wang, Jiuju; Jiang, Yuanling; Si, Yajing; Peng, Wenjing; Song, Limeng; Jiang, Yi; Zhang, Yangsong; Dong, Wentian; Yao, Dezhong; Xu, Peng (Frontiers in Computational Neuroscience, 2018)
Cognitive deﬁcits in schizophrenia are correlated with the dysfunctions of distinct brain regions including anterior cingulate cortex (ACC) and prefrontal cortex (PFC). Apart from the dysfunctions of the intrinsic connectivity of related areas, how the coupled neural populations work is also crucial in related processes. 24 patients with schizophrenia (SZs) and 24 matched healthy controls (HCs) were recruited in our study. Based on the electroencephalogram (EEG) datasets recorded, the Dynamic Causal Modelling (DCM) was then adopted to estimate how the brain architecture adapts among related areas in SZs and to investigate the mechanism that accounts for their cognitive deficits. The distinct winning models in SZs and HCs consistently emphasized the importance of ACC in regulating the elicitations of P300s. Specifically, comparing to that in HCs, the winning model in SZs uncovered a compensatory pathway from dorsolateral PFC to intraparietal sulcus that promised the SZs’ accomplishing P300 tasks. The findings demonstrated that the ″disconnectivity hypothesis″ is helpful and useful in explaining the cognitive deficits in SZs, while the brain architecture adapted with related compensatory pathway promises the limited brain cognitions in SZs. This study provides a new viewpoint that deepens our understanding of the cognitive deficits in schizophrenia.